2020
DOI: 10.1253/circj.cj-19-1177
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of No-Flow Time on 30-Day Neurological Outcomes in Patients With Out-of-Hospital Cardiac Arrest Who Received Extracorporeal Cardiopulmonary Resuscitation

Abstract: Background: How the time sequence of cardiopulmonary resuscitation (CPR) procedures is related to clinical outcomes in patients with out-of-hospital cardiac arrest (OHCA) remains unclear. This study examined the impact of the time interval from collapse to start of CPR (no-flow time, NF time) and the time interval from start of CPR to implementation of extracorporeal CPR (ECPR) (low-flow time, LF time) on neurological outcomes. Methods and Results: During the period from 2010 to 2015, we enrolled 85 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 38 publications
1
16
2
Order By: Relevance
“…Previous studies showed that E-CPR has signi cant bene cial effect on both early patient survival and favorable neurological outcome, [15] [16] Murakami et al recently reported that 30-day neurological outcome can be predicted by the interval from collapse to start of CPR better than the interval from collapse to start E-CPR time. [11] In the current study, we did not investigate the interval from collapse to CPR and the interval from collapse to E-CPR appeared to be shorter (< 36 minutes) than their report in all treatment groups (favorable and unfavorable neurological groups were, 50.1 and 55.1 minutes, respectively [11]). In their study, rates of CPC 1 or 2 of total collapse duration between 0 to 45 minutes were 19.2% and that of ECPELLA in the current study was 31%, whereas IABP + VA-ECMO and VA-ECMO were 13% and 7%, respectively.…”
Section: Discussioncontrasting
confidence: 53%
“…Previous studies showed that E-CPR has signi cant bene cial effect on both early patient survival and favorable neurological outcome, [15] [16] Murakami et al recently reported that 30-day neurological outcome can be predicted by the interval from collapse to start of CPR better than the interval from collapse to start E-CPR time. [11] In the current study, we did not investigate the interval from collapse to CPR and the interval from collapse to E-CPR appeared to be shorter (< 36 minutes) than their report in all treatment groups (favorable and unfavorable neurological groups were, 50.1 and 55.1 minutes, respectively [11]). In their study, rates of CPC 1 or 2 of total collapse duration between 0 to 45 minutes were 19.2% and that of ECPELLA in the current study was 31%, whereas IABP + VA-ECMO and VA-ECMO were 13% and 7%, respectively.…”
Section: Discussioncontrasting
confidence: 53%
“…[15] [16] Murakami et al recently reported that 30-day neurological outcome can be predicted by the interval from collapse to start of CPR better than the interval from collapse to start E-CPR time. [11] In the current study, we did not investigate the interval from collapse to CPR, and the interval from collapse to E-CPR appeared to be shorter (<36 minutes) than their report in all treatment groups (favorable and unfavorable neurological groups were 50.1 and 55.1 minutes, respectively [11]). In their study, the rates of CPC 1 or 2 of total collapse duration between 0 and 45 minutes were 19.2% and that of ECPELLA in the current study was 31%, whereas IABP+VA-ECMO and VA-ECMO were 13% and 7%, respectively.…”
Section: Discussioncontrasting
confidence: 53%
“…Exclusion criteria included 1) apparent aortic dissection prior to the E-CPR; 2) non-cardiac origins including severe trauma and/or stroke; and 3) known poor prognosis or terminal malignancies. 16. , 17.…”
Section: Methodsmentioning
confidence: 99%